Les deux amies: essai sur le couple de femmes dans l'art - Bonnet, Marie-Jo (Éditions Blanche, 2000)
Que montre un artiste lorsqu'il représente un couple de femmes enlacées? C'est la question que pose Marie-Jo Bonnet, spécialiste d'histoire culturelle, en regardant près de 150 tableaux. S'agit-il d'un voyeurisme masculin sans conséquences? S'agit-il de dévoiler l'éros lesbien? Ou s'agit-il de construire un espace symbolique où le désir féminin s'émancipe de la loi phallique?
Keywords: 1900-1999; LGBTQIA2+; approches et analyses; cours; discipline; europe; france; hétéronormativité; hétérosexisme; identités LGBTQIA2+; inégalités; lesbianisme; premier cycle; périodes historiques; queer; régions géographiques; sexualité; shm4000; systèmes d'oppressions; thématiques

Heterosexuals' use of "fag" and "queer" to deride one another: a contributor to heterosexism and stigma - Burn, S M (Journal of homosexuality, 2000)
This paper is on heterosexuals' use of words such as "fag" and "queer" to refer to one another in an insulting manner. This behavior perpetuates heterosexism and the stigmatization of gays. Two hundred and fifty-seven university students (73% Euro-American) served as participants. Males exhibited more anti-gay prejudice and anti-gay behavior than females. Heterosexual males frequently used words such as "fag" and "queer" to put one another down. Anti-homosexual prejudice was predictive of anti-gay behavior. However, approximately half of those who engaged in the behavior were not strongly anti-homosexual. For these individuals, the behavior may win approval from their social group. Awareness campaigns and peer reminders that the derisive use of "fag" and "queer" harms homosexuals may be effective in changing this group. It is more difficult to reduce this behavior in individuals with strong anti-homosexual attitudes. The role of individuals and educational and work organizations in bringing about change is discussed.
Keywords: LGBTQIA2+; approches et analyses; cours; discipline; homophobie; hétérosexisme; insultes; premier cycle; psychologie; sciences humaines; soc2014; systèmes d'oppressions; thématiques

Mort ou fif: la face cachée du suicide chez les garçons - Dorais, Michel; Lajeunesse, Simon Louis (Des hommes et des femmes en changement, 2000)
A partir de témoignages et récits de vie, cet ouvrage met en lumière la relation entre le mépris et l'ostracisme dont sont victimes les adolescents homosexuels ou considérés comme tels et leur haut taux de suicide. Une version revue et corrigée d'un document publié par le Centre de recherche sur les services communautaires de l'Université Laval (octobre 2000).
Keywords: 1900-1999; 1980-1989; 1990-1999; LGBTQIA2+; amérique du nord; amériques; approches et analyses; canada; corps; cours; discipline; hétérosexisme; identités LGBTQIA2+; premier cycle; périodes historiques; queer; québec; régions géographiques; santé; shm4000; systèmes d'oppressions; thématiques

Homosexualités: l'adieu aux normes - Fortin, Jacques (Discorde, 2000)
Adieu à la tyrannie de la norme hétérosexuelle dominante… et adieu aussi à l’antinorme d’une homosexualité à son tour normative. Ni dissolution dans l’indifférence, ni enfermement volontaire dans la célébration d’une différence ! Contre les séparations normatives des idéologies de la différence et contre la ghettoïsation des libertés, Jacques Fortin dessine un horizon où la catégorie d’une homosexualité serait appelée à dépérir dans la diversité et la banalité des pratiques sexuelles. Avec cette position originale et radicale, Jacques Fortin apporte des arguments neufs au débat public : pour l’accès à la parentalité ou pour le vote d’une loi contre l’homophobie.
Keywords: 1900-1999; 1970-1979; 1980-1989; 1990-1999; LGBTQIA2+; approches et analyses; cours; discipline; discours dominant; europe; france; hétérosexisme; identités LGBTQIA2+; premier cycle; périodes historiques; queer; régions géographiques; sexualité; shm4000; systèmes d'oppressions; thématiques

Saint Foucault - Halperin, David M. (Les grands classiques de l'érotologie, 2000)
La pensée de Foucault, marquée par une inébranlable volonté de résister aux normes, peut servir de modèle théorique au mouvement gay. Loin de vouloir construire une « identité gay », il s’agit plutôt d’inventer de nouvelles positions à l’écart de la normalité et de l’hétéronormativité. La vision foucaldienne radicale de l’homosexualité en tant qu’occasion historique de rouvrir des virtualités relationnelles et affectives anticipe la paradoxale politique queer : une identité sexuelle qui s’effectue comme un décalage par rapport à toute visée identificatrice. Halperin propose le premier compte rendu synthétique de la pensée de Foucault concernant la sexualité gay et l’avenir du mouvement lesbien et gay, en même temps qu’un résumé des plus récents travaux de la queer théorie.
Keywords: 1900-1999; 1970-1979; 1980-1989; 1990-1999; LGBTQIA2+; approches et analyses; cours; discipline; discours dominant; europe; france; hétérosexisme; identités LGBTQIA2+; justice sociale; premier cycle; périodes historiques; queer; régions géographiques; sexualité; shm4000; soc2014; systèmes d'oppressions; thématiques

Something to tell you: the road families travel when a child is gay - Herdt, Gilbert H.; Koff, Bruce (Between men--between women, 2000)
Even now, at the end of the twentieth century, many still have difficulty standing up and saying, "I am the parent of a gay child." Something to Tell You recounts the stories of families whose lives have been touched by the discovery that a child is lesbian or gay—how it affects and influences people's perceptions of their children and even changes the self-image of parents themselves. Focusing on fifty average families—not people seen in clinics or therapy—the authors found a consistent pattern of change: first negative, then positive. Sometimes the news led parents and siblings to form stronger bonds with the child, with each other, and with other relatives and friends. In many cases, their child's partner and partner's family grew to assume an important role in their own lives. In some cases, parents and siblings discovered new meaning in their lives through speaking out or joining PFLAG (Parents, Families, and Friends of Lesbians and Gays) and becoming part of the struggle for lesbian and gay rights. The authors found that families committed to staying together are typically able to overcome the powerful obstacles imposed by society. Something to Tell You also shows the lasting and sometimes tragic consequences for families who falter in the process of integration. Unwilling to accept their child's sexuality, some parents sought to blame each other, and all too often their own relationships unraveled as a result. Others who failed to tell close friends sometimes lost those friends through keeping secrets. Parents who neglected to form bonds with their child's partner fostered climates of alienation that persisted for years. A richly diverse collection of family stories, Something to Tell You is a book that will help break down widespread prejudice and put an end to destructive cultural myths. It affirms families' highest aspirations toward active love for their gay children, showing the steps to take toward new levels of support, solidarity, and love.
Keywords: LGBTQIA2+; amériques; approches et analyses; cours; discipline; famille; hétérosexisme; patriarcat; premier cycle; relations familiales; régions géographiques; sciences humaines; soc2014; sociologie; systèmes d'oppressions; thématiques; états-unis